Dermatological toxicity of acute lymphoblastic leukemia treatment by protocol ALL IC-BFM 2002 - Timur T. Valiev; Tatiana S. Belysheva (ZAO "Consilium Medicum", 2022)
Background. Аcute lymphoblastic leukemia (ALL) in children is not only the most common but also potentially curable disease in 8590% cases. The other side of high effectiveness of modern treatment protocols their toxicity. Inspite of skin and mucosal toxicity is not a life threatening condition, it requires a supportive care to prevent infectious complications, which prolong hospitalization, administration of antibacterial, antifungal and in some cases antiviral drugs. Aim. To study skin and mucosal toxicity in patients with ALL, treated by ALL IC-BFM 2002 protocol. Materials and methods. One hundred and nineteen pediatric patients with primary diagnosed ALL were enrolled the study. All the patients were treated by ALL IC-BFM 2002 protocol. Toxicity assessment was performed on each step by the scale of National Cancer Institute (NCI) USA, 2d version. Results. The most often variants of skin and mucosal toxicity during ALL IC-BFM 2002 protocol were found on protocol mM/M, based on high-dosed methotrexate. In 42.1% stomatitis 2st. was diagnosed on methotrexate dose 5000 mg/m2, 3st. 15.8%, 4st. 5,3%. Methotrexate dosed 2000 mg/m2 coused stomatitis 3 st. in 6.3%, in other patients stomatitis was 12st. Exfoliative dermatitis was in 1 (1%) case with prolonged methotrexate elimination. Block polychemotherapy used in high risk group of patients was complicated with stomatitis 34 st. in 90%. In 20% naso-gastral catheter was performed and in 25% used partial/hole parenteral nutrition support. Alopecia was reversible and observed in 100% patients. Protocols I, II and maintenance treatment were free of clinically significant skin and mucosal toxicity. Conclusion. The skin and mucosal toxicity profile of ALL IC-BFM 2002 protocol was tolerable. Hole volume of supportive care, preventing and treatment of dermatological toxicity of chemotherapy can prevent of severe skin and mucosal toxicity (soft tissue infections, sepsis, metabolic disorders).